Design and protocol for the Focusing on Clozapine Unresponsive Symptoms (FOCUS) trial: a randomised controlled trial. Issue 1 (December 2016) - Pyle, Melissa; Norrie, John; Schwannauer, Matthias; Kingdon, David; Gumley, Andrew; Turkington, Douglas; Byrne, Rory; Syrett, Suzy; MacLennan, Graeme; Dudley, Robert; McLeod, Hamish; Griffiths, Helen; et al.
Abstract Background For around a third of people with a diagnosis of schizophrenia, the condition proves to respond poorly to treatment with many typical and atypical antipsychotics. This is commonly referred to as treatment-resistant schizophrenia. Clozapine is the only antipsychotic with convincing efficacy for people whose symptoms are considered treatment-resistant to antipsychotic medication. However, 30–40 % of such conditions will have an insufficient response to the drug. Cognitive behavioural therapy has been shown to be an effective treatment for schizophrenia when delivered in combination with antipsychotic medication, with several meta-analyses showing robust support for this approach. However, the evidence for the effectiveness of cognitive behavioural therapy for people with a schizophrenia diagnosis whose symptoms are treatment-resistant to antipsychotic medication is limited. There is a clinical and economic need to evaluate treatments to improve outcomes for people with such conditions. Methods/design A parallel group, prospective randomised, open, blinded evaluation of outcomes design will be used to compare a standardised cognitive behavioural therapy intervention added to treatment as usual versus treatment as usual alone (the comparator group) for individuals with a diagnosis of schizophrenia for whom an adequate trial of clozapine has either not been possible due to tolerability problems or was not associated with a sufficient therapeutic response. The trial will be conducted across five sites in the United Kingdom. Discussion The recruitment target of 485 was achieved, with a final recruitment total of 487. This trial is the largest definitive, pragmatic clinical and cost-effectiveness trial of cognitive behavioural therapy for people with schizophrenia whose symptoms have failed to show an adequate response to clozapine treatment. Using a prognostic risk model, baseline information will be used to explore whether there are identifiable subgroups for which the treatment effect is greatest. Trial registration Current Controlled TrialsISRCTN99672552 . Registered 29th November 2012.